Editorial [Hot topic: The Hypoxia-Inducible Factor (HIF) Pathway as a Target for Prevention and Treatment of Clinical Manifestations (Executive Editor: Thomas Kietzmann)] - Kietzmann, Thomas (Current Pharmaceutical Design, 2009)
Within the last decade it became evident that a family of hypoxia-inducible transcription factors (HIFs) are key players in the cellular response to limited O2 supply. From the three HIFs known today, HIF-1 is the best characterized and it appears to be of special interest since it activates transcription of glycolytic enzymes and glucose transporters as well as angiogenic growth factors to improve nutrient and blood supply to meet the energy demands of the cell. Thus, HIFs appear to have a central role in the adaptive cellular program responding to hypoxia in normal tissues. HIFs are heterodimers composed of α- and ß-subunits, the latter also known as the ARNT proteins. While the levels of the β-subunits seem to be quite stable, the α-subunit levels are low under normoxia and upregulated under hypoxia. Thereby transcriptional, posttranscriptional and posttranslational processes are involved. From the latter, the oxygen-dependent hydroxylation of proline 402 and 564 followed by the binding of the von Hippel-Lindau (VHL) protein initiates degradation of HIF-1α by the ubiquitin-proteasome system whereas hydroxylation at asparagine 803 initiates loss of the coactivator p300/CBP. Importantly, hypoxia is also a major feature of a number of diseases and almost all solid tumors contain hypoxic regions in which O2 concentrations are greatly reduced compared to the surrounding normal tissue. Further, a number of studies from various tumor entities showed that increased levels of HIFs, especially HIF-1α are associated with a poor prognosis. Thus, tumor cells survive and proliferate under extreme conditions where nutrients and oxygen are limited, and HIFs initiate the expression of various genes wich increase the risk of patient mortality. In addition, many studies focused on the understanding of cancer progression have shown that HIF α-subunits also respond to growth and coagulation factors, hormones, cytokines or stress factors under non-hypoxic conditions. Altogether this increased the interest in HIF α-subunits, especially HIF-1α, as a drug target and new, specific therapeutic strategies targeting the HIF pathway are intesively investigated.